A Low Cost Shading Analyzer and Site Evaluator Design to Determine Solar Power System Installation Area - Selami Kesler; Sinan Kivrak; Hilmi Gurleyen; Furkan Dincer; Saban Yilmaz; Hasan Riza Ozcalik (International Journal of Photoenergy)
Shading analyzer systems are necessary for selecting the most suitable installation site to sustain enough solar power. Afterwards, changes in solar data throughout the year must be evaluated along with the identification of obstructions surrounding the installation site in order to analyze shading effects on productivity of the solar power system. In this study, the shading analysis tools are introduced briefly, and a new and different device is developed and explained to analyze shading effect of the environmental obstruction on the site on which the solar power system will be established. Thus, exposure duration of the PV panels to the sunlight can be measured effectively. The device is explained with an application on the installation area selected as a pilot site, Denizli, in Turkey.